Maxillofacial Fracture Experiences: A Review of 152 Cases - Osman Enver Aydin (Eurasian Journal of Medicine, 2012)
Objective: The fractures of facial structures lead to great morbidity. Cross-sectional studies are needed to evaluate the current state of maxillofacial traumas. Thus, this study aims to evaluate these experiences and to compare these results with the current literature.Materials and Methods: The medical records of the maxillofacial fracture cases hospitalized between January 2004 and November 2011 were examined. The age, sex, etiology, fracture localization and treatment method for each case were documented. The affected facial bones were grouped as mandible, maxilla, zygoma, naso-orbitoethmoid complex (NOEC) and blow-out. Nasal fractures were excluded. The cases were assigned to 3 groups with respect to age (below 16, above 65 and between 17 and 64). The chi Square test was used to assess the significance of the difference in mandibular fracture rates in the pediatric population compared to others.Results: The total number of cases was 152. The total number of fractures was 185. Of the 152 cases, 117 were male and 35 were female. The average age was 31.4 (±18.3), ranging between 2 and 81. Thirty-one cases were 16 years old or less. Nine cases were 65 years old or more. Mandibular and zygomatic fractures were the most prevalent fractures in the adult group. Mandibular fractures were significantly more common in the pediatric age group compared to rest of the population (X2, p<0.05). Traffic accidents were the most common etiological factor, with a 55.3% ratio. Open reduction and internal fixation was the most frequently conducted treatment modality in all age groups. Conclusion: Retrospective studies are important for the projection of future prospects. In summary, our results indicate that pediatric fractures are mostly in the lower face and usually affect the condylar region, which is consistent with the literature.